(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2014)
This research aimed to find out the improvement of the students’ pronunciation ability by using Substitution Drill that focused on English Consonants which consisted of dental and palato alveolar consonants and English Vowel which consisted mid-front,mid-central and mid-back vowel. The researcher applied Pre-Experimental method with one group pretest-posttest design and collected the data by giving pre-test and post-test. The sample of the research was class X IPA of SMA Negeri 1 Galesong Selatan which consisted of 33 students. The sample was taken by using the purposive technique. The research variables were teaching pronunciation by using Substitution Drill as an independent variable and dependent variable were English Consonants and English Vowel. The result of the research showed that the tenth-grade students of SMA Negeri 1 Galesong Selatan had fair score in the pre-test. After treatment, their pronunciation ability significant improved. The result of the research was the mean score obtained by the students through pre-test was 5.77 which was classified as fair classification and the mean score of the students on the post-test was 7.32 which was classified as good classification and the value of t-test was greater than t-table (16.48 > 2.037). It indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. It was concluded that the use of Substitution Drill was effective to improve the students’ pronunciation ability. Keywords: improvement, pronunciation, substitution drill, dental, palato alveolar